2021
DOI: 10.1002/cpt.2177
|View full text |Cite
|
Sign up to set email alerts
|

RAAS Blockade and COVID‐19: Mechanistic Modeling of Mas and AT1 Receptor Occupancy as Indicators of Pro‐Inflammatory and Anti‐Inflammatory Balance

Abstract: ACE inhibitors (ACEis) and angiotensin receptor blockers (ARBs) are standard-of-care treatments for hypertension and diabetes, common comorbidities among hospitalized patients with coronavirus disease 2019 (COVID-19). Their use in the setting of COVID-19 has been heavily debated due to potential interactions with ACE2, an enzyme that links the pro-inflammatory and anti-inflammatory arms of the renin angiotensin system, but also the entryway by which severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Recently it was shown that the membrane-bound ACE2 acts as a receptor for SARS-CoV-2 but it is still under investigation the possible effects on RAS components (AngII, Ang1-7, ACE, ACE2, AT1 and Mas) and whether ACEi and ARBs interfere with the mitigation of COVID-19. [35, 36, 37, 38, 39] Considered that COVID-19 and other infectious diseases have a major impact in aged adults, mainly in those with chronic diseases (i.e. hypertension and users of ACEi or ARBs), our results bring new intriguing questions regarding the link between ACE expression in immune cells, inflammaging and immunosenescence and perspectives for drug development/repurposing.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently it was shown that the membrane-bound ACE2 acts as a receptor for SARS-CoV-2 but it is still under investigation the possible effects on RAS components (AngII, Ang1-7, ACE, ACE2, AT1 and Mas) and whether ACEi and ARBs interfere with the mitigation of COVID-19. [35, 36, 37, 38, 39] Considered that COVID-19 and other infectious diseases have a major impact in aged adults, mainly in those with chronic diseases (i.e. hypertension and users of ACEi or ARBs), our results bring new intriguing questions regarding the link between ACE expression in immune cells, inflammaging and immunosenescence and perspectives for drug development/repurposing.…”
Section: Discussionmentioning
confidence: 91%
“…Recently it was shown that the membrane-bound ACE2 acts as a receptor for SARS-CoV-2 but it is still under investigation the possible effects on RAS components (AngII, Ang1-7, ACE1, ACE2, AT1 and Mas) and whether ACEi and ARBs interfere with the mitigation of COVID-19. [50, 51, 52, 53, 54] Therefore, it is important to emphasize the negative impact of chronic diseases for the outcome of older adults during a viral infection and how ACE1/ACE2 expression in immune cells could bring information to diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 88 , 89 It is the result of high affinity of SARS‐CoV2 to critical components of the ACE2 axis compared to the AT1 receptor axis, resulting in a hyperinflammatory state of RAAS. 90 , 91 , 92 , 93 Physiologically, it should be noted that the RAAS belongs to the blood pressure controlling part of the endocrine system; but it also has these effects on inflammation. Integrating RAAS into the conceptualisation of the immune system with its pro‐ and anti‐inflammatory functions and its innate and adaptive cellular components in the view of a systemic functional analysis leads to a network model with imbalanced interactions, resulting in a hyper‐inflammatory state of the cellular matrix (Figure 3 ).…”
Section: Systemic Physiology and Pathologymentioning
confidence: 99%
“…Neyrinck et al [ 184 ] demonstrated that ACEI had a therapeutic effect on endotoxin-induced lung injury in rats. Melissa et al [ 185 ] showed that ACEI and ARBs might improve ARDS by inhibiting the ACE/Ang II/AT1R signaling pathway. ARBs inhibited the canonical RAS pathway through angiotensin /Ang II/ATR1 axis; increasing ACE2, TLR-2, and IL-1β; and causing accumulation of reactive oxygen species (ROS), while ACE2 upregulation activates Ang-(1-7)/Mas pathway and inhibits inflammatory signals [ 186 ].…”
Section: The Potential Therapeutic Role Of Ace2 In Covid-19mentioning
confidence: 99%